Pengabdian kepada Masyarakat melalui RRI Tarakan, Mozaik Indonesia : Digital Marketing untuk Palaku UMKM - Syaddam; Mangande, Hariyanto (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
MSMEs play a vital role in the Indonesian economy, contributing around 60% of the Gross Domestic Product. However, many MSMEs still face challenges in utilizing digital technology to effectively market their products and services. This community service activity aims to increase the understanding and capabilities of MSME actors in implementing digital marketing strategies. Through an interactive talk show session at RRI Tarakan, resource persons from Politeknik Bisnis Kaltara shared knowledge and experience on the use of social media, website optimization, and the use of e-commerce platforms. This strategy is aimed at expanding market reach, increasing product visibility, and strengthening customer relationships. By participating in this activity, it is hoped that MSME actors can increase their competitiveness and business growth using digital technology in their marketing strategies. In addition, this activity can also encourage the sustainability of the program in the future by involving key stakeholders, such as local governments and universities. This collaboration is expected to be able to design programs that are in line with the needs and challenges faced by MSMEs, so that it can help improve the ability of MSME actors to utilize digital technology to develop their business.